Variability in Executive Control Performance Is Predicted by Physical Activity - Gooderham, G. Kyle; Ho, Simon; Handy, Todd C. (Frontiers in Human Neuroscience, 2020)
Physical activity (PA) promotes neurogenesis and has neuroprotective effects on the brain, bolstering the structural and functional resources necessary for improved cognitive functioning. Intraindividual variability (IIV) in cognitive performance is linked to neuropsychological structure and functional ability. Despite evidence of the neurogenerative and neuroprotective effects of PA, limited investigation into the link between PA and IIV has been conducted. Across three studies we investigate the effect of PA on IIV in reaction time (RT) on three modified Flanker Tasks. The International Physical Activity Questionnaire was used to evaluate PA while the Attention Network Test (ANT) and two additional modified Flanker Tasks were used to assess executive control and attentional performance. Reaction Time Coefficients of Variation (RTCV) were calculated for each participant by dividing the standard deviation by the mean RT for each stimuli condition. Analysis revealed that basic RT was not associated with PA nor was PA predictive of IIV on the modified Flanker Tasks. However, three consistent findings emerged from analysis of the ANT. First, RTCV and moderate PA were positively related, such that more self-reported moderate PA was associated with greater IIV. Conversely, RTCV and vigorous PA were negatively related. Finally, when controlling for the effects of PA on IIV in young adults, variability decreases as age increases. In sum, PA is predictive of IIV on attentional and executive control tasks in young adults, though only at particular intensities and on certain tasks, indicating that task type and cognitive load are important determinants of the relationship between PA and cognitive performance. These findings are consistent with prior literature that suggests that the role of PA in young adults is reliant on specific interventions and measures in order to detect effects more readily found in adolescent and ageing populations.